Analysis of Benefits, Ease of Use, and Security on Interest in Using the Gojek Application in West Java - Dina Yulia Wijaya; Hari Imbrani; Hani Rosita; Yuliani Istiqomah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the impact of Perceived Benefits, Ease of Use, and Security on User Interest in using the Gojek application. As the ride-hailing and on-demand services industry becomes increasingly competitive, understanding what drives user interest is crucial for the continued growth of Gojek. The research adopts a quantitative approach, using primary data obtained from an online questionnaire distributed to 106 Gojek users in the West Java region. Path analysis, performed with SPSS statistical software version 26, was employed to test the relationships between the variables. The findings reveal that Perceived Benefits have a significant positive effect on User Interest, indicating that users are more likely to engage with the application if they perceive tangible advantages such as cost savings, convenience, and service variety. Furthermore, Perceived Ease of Use was found to have a positive influence on User Interest, meaning that users are more inclined to use the Gojek application if it is user-friendly and easy to navigate. Additionally, Perceived Security was another important factor, with a positive impact on User Interest. Users who feel that their personal data is secure and their transactions are protected are more likely to continue using the application. These results emphasize the importance of enhancing perceived benefits, ease of use, and security to increase user interest and engagement with the Gojek application. The practical implications of this study suggest that Gojek should focus on improving the user experience by ensuring that users perceive value in the services offered, enhancing usability, and strengthening security measures. As competition in the app-based services industry intensifies, addressing these factors could be key to attracting and retaining more users.